g-factors of some excited states in 49,50Cr - Pakou, A. A.; Billowes, J.; Mountford, A. W.; Tenreiro, C.; Warner, D. D. (HNPS Advances in Nuclear Physics, 2019)
Magnetic moments of the first excited states in 50Cr and of the 7/2" and 19/2' states in 49Cr, have been measured by the transient field technique. The states were excited by the inverse reaction 40Ca + 12C and the recoil nuclei traversed a thick gadolinium foil. The observed rotations, of the 2+, 4+, 6+, 8+ states of the ground-state band in 50Cr, were found into the experimental error to be the same, suggesting similar g-factors for these states and thus supporting a high collectivity for the ground-state band, g-factors of the 7/2' and 19/2 states in 49Cr, were deduced by adopting both an overall parametrization of the transient magnetic field in Gd and by comparing the 49Cr rotations with rotations of states with known magnetic moments, as the 2+ ones of 50Cr and of 46Ti which was also populated in the same reaction. Both methods gave similar results and the g-factors adopted for the 19/2" and 7/2" states were + 0.78(17) and +0.35(7) respectively. These results are discussed in terms of cranked shell model calculations and are found to support a proton alignment in the f7/2 shell.